Hyperglycemia‐mediated oocyte TET3 insufficiency predisposes offspring to glucose intolerance. Issue 10 (29th July 2022) - Wu, Xiumei; Xu, Suowen; Weng, Jianping
Abstract : In a recent article published in Nature, Chen et al. reported that pregestational hyperglycemia rendered offspring vulnerable to glucose intolerance due to insufficient TET3‐mediated 5‐methylcytosine oxidation and DNA demethylation, resulting in hypermethylation and reduction of insulin‐secreting genes.